Educational performance between the human resource's theoretical paradigm and the practical mentality. Analysis at the European level - Ionescu, Romeo Victor; Zlati, Monica Laura; Antohi, Valentin Marian; Cristache, Nicoleta; Raducan, Monica (Frontiers in Psychology, 2022)
The issue of performance in education is always topical because it plays an important role in creating the most valuable resource: labor. It has been treated both from a scientific and practical point of view through numerous strategies and optimization techniques, being integrated with the strategies for educational development as a training system at a global level. This research aimed to identify the need for performance and assessed the theoretical and practical dimensions of the European gap in performance in education, given the impact of the global crisis. The analysis was based on a structured questionnaire that is part of a pilot research in which 130 teachers and school managers from Romania and 97 teachers and school managers from five other European countries participated. The results of the study will allow the identification of the human resource's theoretical paradigm and the practical mentality in the education system to improve performance, which the authors propose to use to identify concrete applicable measures in the short term.